Opinion Leader Communication Networks in Forming Public Opinion on the 100-Day Performance of President Joko Widodo and Vice President Ma'aruf Amin on Twitter - Indri Wisudawati Patiung; Reza Safitri; Maulina Pia Wulandari (International Journal of Science and Society, 2022)
The role of social media such as Twitter can be a means of public space to provide criticism of political activities so that political issues on Twitter have a significant impact on how the public perceives political developments in government. This study aims to find out the most influential people or Twitter accounts in the process of forming public opinion. And to identify the communication network that exists between opinion leaders through accounts on social media Twitter regarding the issue of the 100 days of the performance of the Jokowi-Ma'ruf Amin Government. This study uses exploratory research methods with the help of Big Data analysis. This study wants to show that there is a communication network between opinion leaders that is formed so that it can influence the process of forming public opinion. Based on the research results, the communication network between opinion leaders is divided into two, namely the coalition camp and the opposition camp. The coalition and opposition camps have a close or distance relationship that is intertwined based on the political background of each actor. As well as analysis of conversations on Twitter, it shows that 100 days of Jokowi's performance has reaped many pros and cons, both opinion leaders and public opinion